Marek’s disease vaccines-induced differential expression of known and novel microRNAs in primary lymphoid organ bursae of White Leghorn - Zhang, Lei (Vet Res, 2020)
Marek’s disease (MD) is a contagious disease of domestic chickens caused by MD viruses. MD has been controlled primarily by vaccinations, yet sporadic outbreaks of MD take place worldwide. Commonly used MD vaccines include HVT, SB-1 and CVI988/Rispens and their efficacies are reportedly dependent of multiple factors including host genetics. Our previous studies showed protective efficacy of a MD vaccine can differ drastically from one chicken line to the next. Advanced understanding on the underlying genetic and epigenetic factors that modulate vaccine efficacy would greatly improve the strategy in design and development of more potent vaccines. Two highly inbred lines of White Leghorn were inoculated with HVT and CVI988/Rispens. Bursa samples were taken 26 days post-vaccination and subjected to small RNA sequencing analysis to profile microRNAs (miRNA). A total of 589 and 519 miRNAs was identified in one line, known as line 6(3), 490 and 630 miRNAs were identified in the other, known as line 7(2), in response to HVT or CVI988/Rispens inoculation, respectively. HVT and CVI988/Rispens induced mutually exclusive 4 and 13 differentially expressed (DE) miRNAs in line 6(3) birds in contrast to a non-vaccinated group of the same line. HVT failed to induce any DE miRNA and CVI988/Rispens induced a single DE miRNA in line 7(2) birds. Thousands of target genes for the DE miRNAs were predicted, which were enriched in a variety of gene ontology terms and pathways. This finding suggests the epigenetic factor, microRNA, is highly likely involved in modulating vaccine protective efficacy in chicken.